Investigation on the effect of current density on porous GaN fabricated by UV-assisted electrochemical etching / Nurul Syuhadah Mohd Razali …[et al.] - Mohd Razali, Nurul Syuhadah; Abd Rahim, Alhan Farhanah; Radzali, Rosfariza; Mahmood, Ainorkhilah (Universiti Teknologi MARA, 2021)
This paper reported the anodization of porous GaN by UV-assisted electrochemical etching with a usage of lower power of UV light in an electrolyte that consist of 4% potassium hydroxide (KOH) with a variations of applied current density (20, 30 and 40 mA/cm2 ). Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-Ray (EDX), Atomic Force Microscopy (AFM) and X-ray Diffraction (XRD) were used to characterize the morphological and structural characteristics while the Raman spectroscopy was used to identify the optical properties of the prepared porous GaN. Top view images from the FESEM demonstrated that the pore uniformity and porosity are affected significantly by the current density. The porous GaN sample etched with 40 mA/cm2 produces a higher porosity and larger diameter pore structure compared to other porous GaN sample. This shows that the morphology and structural characteristic of porous GaN are increase with the increase of current density. The EDX result revealed there is no contamination occur, as only significant Ga and N atom presence in all samples. The AFM verified that the surface roughness and the pore depth are increased as current density increased. There were relatively large variations of the peak intensities for 2Thetascan patterns as exposed by XRD. Raman intensity found to be enhanced with the increase in current density and among the porous GaN sample, the peak for sample fabricated with 30 mA/cm2 and 40 mA/cm2 was observed to be slightly shifted to lower frequency.